Lung ultrasound in young children with neurological impairment: A proposed integrative clinical tool for deaeration-detection related to feeding - Fiori, Simona; Moretti, Elena; Amador, Carolina; Martinelli, Alice; Scaramuzzo, Rosa Teresa; Controzzi, Tiziana; Battini, Roberta; Filippi, Luca; Guzzetta, Andrea; Gargani, Luna (Frontiers in Pediatrics, 2022)
Infants and children with neurological impairment, such as cerebral palsy (CP), often experience abnormal ingestion functions, including oropharyngeal dysphagia and gastroesophageal reflux disease, which led to aspiration-related respiratory complications, morbidity, hospitalization or death. There is a lack of evidence-based, repeatable, infant-friendly instrumental procedures to assess aspiration-risk in infants with CP or other neurological disorders, with also a lack of clinical assessment measures to support the use of more invasive diagnostic techniques. To this purpose, in the current study we explore the feasibility of lung ultrasound (LUS), to assess lung deaeration possibly related to aspiration during meal, in a cohort of 35 subjects affected by CP or other encephalopathies, and 10 controls in the same age-range. We coupled LUS procedure with meal caregiver administration for each child. Our results support the feasibility of this innovative approach in the clinical setting. Exploratory findings revealed a number of lung abnormalities likely related to abnormal ingestion function in subjects. Subgroup analyses revealed possible differences in LUS abnormalities between CP and other encephalopathies, possibly related to different mechanism of disease or dysfunction. Also, some evidences arose about the possible relationship between such LUS abnormalities and feeding and swallowing abilities in CP or other encephalopathies. LUS showed preliminarily feasibility and effectiveness in detecting meal-related LUS abnormalities in a dynamic manner in the clinical setting. This approach demonstrated usefulness as a potential tool for improving assessment and management in complex care of infants and young children with severe neurological disorders.